The impact of women-owned micro finance groups in reducing rural poverty in Masvingo: a case of ward 20 in Bikita District. - Pomerai, Matilda (Midlands State University, 2017)
The purpose of this research was to assess the role played by Fushai women-owned micro finance groups in reducing poverty in Bikita ward twenty. The objectives of the research were to examin the extent to which women owned micro finance groups have facilitated the reduction of poverty in rural areas, to examine models of rural micro finance and how they are run and to identify the challenges encounted by micro finance institutions, clients and staff in providing and accessing rural micro finance. Women have built better houses which they could not afford before joining Fushai. Most of the members also use the proceeds from the micro finance project to send their children to school and buy food for the family. Very few women have managed to start income generating projects with the proceeds from Fushai. However the results revealed that internal conflicts can lead to the group being destroyed. The micro finance group activities are time consuming and laborious therefore there is need for group members committed and be cooperative. Member share interests as profits and contributions return to the bank for continued borrowing.